PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU SD NEGERI DI KECAMATAN DELTA PAWAN KABUPATEN KETAPANG - B11109031, RUSMA ANDRIYANI (Jurnal Manajemen Update, 2015)
This Study aimed  to test and analysis  the influence of achievement,   recognition, the work it self,   responsibility  and Advancement on the  performance of teachers at State Elementary Schools in Delta Pawan Sub-Distri, Ketapang. This Research used  the quantitative analysis method because the  research data in the form  of  figures and analysis employed statistic. Samples used  in this study were all a permanent employess with a total of 56 people. The analysis tecnique used was the multipe regression. The analysis and discussion in this study  concluded  that Achievement (X1)  partially had  no significant influence on the employess’ performance;  Recognition (X2)  partially  had a influence on the employess’  significant influence on the empoyess’ performance;  The Work it self  (X3) partially had  no significant influence on the employess’ performance;   Responsibility (X4) partially had  no significant influence on the employess’ performance;  (X5) partially had  no significant influence on the employess’ performance; Keywords : Work Motivation, teachers  performance